ANALISIS KESALAHAN PENGGUNAAN DIKSI OLEH PEMBINA APEL DI SMP NEGERI 1 TOMA - Bazikho, Krismanda (Universitas Nias Raya, 2025)
This research was motivated by researchers' interest because they had problems regarding the inappropriate use of diction when speaking. So, researchers conducted research on analyzing errors in the use of diction by apple coaches. This is due to several factors, namely limited mastery of vocabulary, the habit of using Indonesian inappropriately, lack of proper knowledge of the language in a formal environment. Diction is an important thing to pay attention to when communicating. Because good words when speaking will have a positive impact on the listener. One of the speaking activities is when speaking at the morning assembly activity. There are many speaking activities, one of which is being a supervisor at school. The aim of this research is to describe diction errors by the supervisor of Apel SMP Negeri 1 Toma, Toma District, Academic Year 2023/2024. The method used in this research is a qualitative research method with a descriptive approach. Based on the results of the research, there were (3) types of errors in the use of diction, namely errors in the use of antonym diction, there were (2) data, errors in the use of synonymous diction, there were (6) data. , and errors in the use of non-standard diction are found in (6) data. The total number is (14) data. Based on the research results, the researcher suggests (1) Indonesian language teachers use this diction as material in delivering material about diction as a teaching medium. (2) The researcher advises readers to apply the use of diction to their daily lives, not just memorizing theory, but taking lessons about the use of important diction from each speaker at an event. (3) It is hoped that this research will motivate readers to study other aspects of the use of diction. If necessary, students of the Indonesian Language and Literature Education study program should empower the study of this research as a form of appreciation activity.